Association of mixed tobacco and nicotine exposure with hematological parameters and serum ferritin: a cross-sectional study of young adults at Badr University in Cairo (BUC), Egypt - Amany M. Elshamy; Sandra S. Samy; Mariam A. El Shater; Shahd M. Fouad; Farah M. El Sayed; Ali M. Khalil; Hanaa A. Amer (The Egyptian Journal of Internal Medicine, 2026)
Abstract Smoking remains one of the most serious public health concerns, increasing the risk of several diseases, including cardiovascular disease, stroke, chronic respiratory diseases, and cancer. Carbon monoxide (CO), a toxic byproduct of tobacco smoke, induces hypoxia and subsequently stimulates erythropoiesis as a compensatory response. Therefore, this study aimed to assess the hematological parameters of university students who smoke and elucidate the physiological impact of tobacco smoking for awareness efforts. Methods A total of 200 students and staff aged 19–30 years were recruited from the School of Allied Health Science at Badr University in Cairo (BUC) from July to September 2025. The participants were divided into a smoker group ( n = 100) and a nonsmoker control group ( n = 100). Complete blood count (CBC), ferritin level as an acute-phase reactant protein, and erythrocyte sedimentation rate (ESR) were measured, and the results were compared between the groups. Results A highly statistically significant difference was found between smokers and nonsmokers in hemoglobin (Hb) and ferritin levels, mean corpuscular volume (MCV), and red blood cell (RBC), white blood cell (WBC), and platelet (PLT) counts. Smokers exhibited significantly higher Hb and ferritin concentrations, MCV, and RBC and WBC counts (all p < 0.001). Conversely, the median platelet count was significantly lower in smokers than in nonsmokers (221 × 103/µl vs 269 × 103/µl; p < 0.001), while ESR results showed no significant differences between groups. Conclusion Smoking was associated with significant alterations in the hematological profile and iron metabolism among university students. These findings provide potential insights for clinical practitioners to consider smoking status when interpreting routine hematological parameters. Moreover, the inclusion of hematological health education during awareness may support early smoking cessation initiatives targeting young adults.